BUILDING RESILIENT ENTERPRISE SYSTEMS: A PRACTICAL GUIDE TO SCALABLE MICROSERVICES AND EVENT-DRIVEN ARCHITECTURES - Dharga Panduranga Kolla, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive article explores the evolution and implementation of resilient enterprise systems through the lens of scalable microservices and event-driven architectures. The article examines how modern enterprise architectures have transformed from monolithic systems to distributed, loosely coupled frameworks that better serve contemporary business needs. Through detailed analysis of implementation patterns, performance metrics, and real-world case studies, this article demonstrates the significant impact of microservices and event-driven architectures on system reliability, scalability, and operational efficiency. The article investigates core architectural components, implementation strategies, resilience patterns, and performance optimization techniques while highlighting successful applications across various industry sectors, including e-commerce, financial services, and logistics. Additionally, it addresses common challenges in implementing these architectures and provides proven solutions for organizations undertaking digital transformation initiatives. The article concludes with an examination of emerging trends and future directions in enterprise architecture, emphasizing the growing importance of artificial intelligence, edge computing, and advanced observability solutions in shaping the next generation of enterprise systems.